(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate whether health courses of the Central-West region of Brazil offer educational videos as a complementary teaching tool and to analyse whether the characteristics of the videos influence user engagement. The e-mec platform databank was used to access information from 295 health courses. Simultaneously, basic histology videos were created and offered freely on YouTube. It was observed that there is a demand for free health educational videos. However, no videos were found on health courses websites. It was found that videos of up to 1 min present better user retention (83%) than longer videos (58%) and that smartphones are not the preferred device to access educational videos online (p <0.05). It was concluded that the videos are underused as a complementary teaching tool by health courses in the Central-West region and that their duration influences the way users will engage the online content.